Pengaruh Work-Life Balance, Perceived Organizational Support dan Kepuasan Kerja Terhadap Organizational Citizenship Behavior - Muhammad Yusuf Hasibuan; Zulvia Khalid (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Human resources are a strategic asset for an organization because they play a crucial role in increasing the effectiveness and sustainability of the organization, one of which is through Organizational Citizenship Behavior (OCB). OCB is influenced by various factors, both internal and external, including work-life balance, perceived organizational support, and job satisfaction. This study aims to analyze the influence of work-life balance, perceived organizational support, and job satisfaction on OCB among employees of PT Asuransi BRI Life, Jakarta Regional Office 3. This study used a quantitative approach with a causal associative approach. The sample size was 75 employees, selected using a saturated sampling technique. Data were collected using a five-point Likert scale questionnaire and analyzed using multiple linear regression using Microsoft Excel 2021 and IBM SPSS version 22.0. The results showed that partially, work-life balance had a positive and significant effect on OCB, while perceived organizational support and job satisfaction did not significantly influence OCB. However, simultaneously, all three variables significantly influenced OCB.